A Primer on a Comprehensive Genetic Approach to Vascular Anomalies - Borst, Alexandra J.; Nakano, Taizo A.; Blei, Francine; Adams, Denise M.; Duis, Jessica (Frontiers in Pediatrics, 2020)
The field of vascular anomalies has grown tremendously in the last few decades with the identification of key molecular pathways and genetic mutations that drive the formation and progression of vascular anomalies. Understanding these pathways is critical for the classification of vascular anomalies, patient care, and development of novel therapeutics. The goal of this review is to provide a basic understanding of the classification of vascular anomalies and knowledge of their underlying molecular pathways. This provides an organizational framework for phenotype/genotype correlation and subsequent development of a diagnostic and treatment roadmap. With the increasing importance of genetics in the diagnosis and treatment of vascular anomalies, we highlight the importance of clinical geneticists as part of a comprehensive multidisciplinary vascular anomalies team.